Реакция цианобактерии Calothrix sp. ISC 65 из загрязненных нефтью регионов на комплексное воздействие солености, дефицита углерода и низкой освещенности - Амирлатифи, Х.С.; Шокрави, Ш.; Сатей, А.; Гольсефиди, М.А.; Махмудджанло, М. (Альгология, 2018)
Изучены физиологические реакции цианобактерии Calothrix sp. ISC 65, выделенной из почвы вблизи Персидского залива, на комбинированное воздействие разной солености среды (0; 0,5 и 1,0%), слабой освещенности (2 μE•м⁻²•с⁻¹) и низких концентраций углекислого газа (при отсутствии аэрации и дополнительной подачи СО₂). Epidaphic and endaphic cyanobacteria of oil polluted regions of southern Iran live under extreme environmental conditions including extremely low irradiance, limited carbon dioxide concentration and high degrees of salinity. Calothrix sp. ISC 65 is an unexplored strain which seems common in southern Iran and near the Persian-Gulf. Until now, we have no report about the basic and applied aspects of such a strain. In this research Calothrix sp. ISC 65 has been characterized physiologically by the combination of extremely low irradiance (2 µE•m⁻²•s⁻¹), different salinities (0%, 0.5%, and 1%), and extremely limited carbon dioxide concentration (no aeration, no carbon dioxide enrichment).